Testing climate models for agricultural impacts: recent trends, current projections, crop-climate suitability, and prospects for improved climate model information - Washington, R.; New M; Hawcroft, M.; Pearce H; Rahiz M; Karnacharya J (2012)
Good climate projections for agriculture can help guide investments in risk management and adaptation. New reports offer insights into the reliability of future climate projections for agriculture, and show how to make the most of current data.